Struggle for Right to Health Equity and Social Justice: Remembering Professor David Sanders - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2019)
Professor David Sanders, a well-renowned academic, consummate activist and commentator, a great public intellectual passed away on 30th August 2019 at the age of 74 years. He was a champion of economic and social justice and one of the pioneers of the importance of primary health care who emphasized the importance of involving communities, being accountable to communities and role of community health workers in promoting health and preventing disease. David shaped research and teaching in public health for almost five decades. This paper highlights David's contribution in public health teaching, research and advocacy. Keywords: Public intellectual, People's Health Movement, Struggle for Health, David Sanders